Perencanaan dan Pengembangan Aplikasi Absensi Mahasiswa Menggunakan Smart Card Guna Pengembangan Kampus Cerdas - Santoso Santoso; Radna Nurmalina (JURNAL INTEGRASI, 2017)
Politeknik negeri tanah Laut is currently the only college which is located in the district of Tanah Laut. One of the campus activities is learning and teaching, student when enter to class sign in paper, the activities need more times and papers because the quantity of students. This application record the hand sign data to database. Applications are made to capable of storing the data attendance lectures when in the class room. Using smartcard included Radio Frequency Identification (RFID) on the card, the application stored data in the database system, to facilitate reporting, applications built to provide reports activities, and the reports can be printed. based measurement RFID cards and readers, the result RFID card reading capability of approximately ± 2seconds, with accuracy of 98 percent.